2004
DOI: 10.1016/j.cub.2004.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: A helix of ankyrin repeats of the NOMPC-TRP ion channel is the gating spring of mechanoreceptors

Abstract: rich rock increases local field strength enough to alter map readings but not compass direction, should leave the birds reoriented or disoriented. Indeed, at smooth gradients they are reoriented, whereas at irregular ones they are ludicrously disoriented (Figure 3).Pigeons, like most animals with maps, possess enormous numbers of magnetite grains in the ethymoid sinus. There are species in which magnetic sensitivity may be mediated in other ways, for example magnetic induction in elasmobranchs, or paramagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 16 publications
6
140
0
2
Order By: Relevance
“…The elongated structures of these molecules suggest a linear reaction coordinate that naturally aligns with the unidirectional retraction coordinate used in force spectroscopy. In some cases, the application of force along the long axis of linear repeat proteins may be biologically relevant, as some linear repeat-containing proteins have been proposed to act as mechanical springs within the cell [97][98][99][100][101].…”
Section: Forced Unfolding By Afmmentioning
confidence: 99%
See 1 more Smart Citation
“…The elongated structures of these molecules suggest a linear reaction coordinate that naturally aligns with the unidirectional retraction coordinate used in force spectroscopy. In some cases, the application of force along the long axis of linear repeat proteins may be biologically relevant, as some linear repeat-containing proteins have been proposed to act as mechanical springs within the cell [97][98][99][100][101].…”
Section: Forced Unfolding By Afmmentioning
confidence: 99%
“…The elongated structures of these molecules suggest a linear reaction coordinate that naturally aligns with the unidirectional retraction coordinate used in force spectroscopy. In some cases, the application of force along the long axis of linear repeat proteins may be biologically relevant, as some linear repeat-containing proteins have been proposed to act as mechanical springs within the cell [97][98][99][100][101].Forced unfolding studies of Ankyrin-B, a 24 repeat cytoskeletal protein have revealed two different forced unfolding events [97]. At low extensions, a linear force-displacement relationship is seen up to forces of 100pN, which the authors interpret as Hookean distortion of a fairly rigid superhelical ankyrin stack.…”
mentioning
confidence: 99%
“…Visual inspection of the extrapolated structure of 24 ankyrin-R repeats 2 indicates the possibility of spring-like behaviour of the putative superhelix. Moreover, stacks of 17-29 ankyrin repeats in the cytoplasmic domains of transient receptor potential (TRP) channels have been identified as candidates for a spring that gates mechanoreceptors in hair cells as well as in Drosophila bristles [3][4][5] . Here we report that tandem ankyrin repeats exhibit tertiary-structure-based elasticity and behave as a linear and fully reversible spring in single-molecule measurements by atomic force microscopy.…”
mentioning
confidence: 99%
“…For the chloroplast protein SRP43 it has been shown that its third and fourth ANK repeats are involved in dimerization of the protein (Jonas-Straube et al 2001) and two recent studies demonstrate the importance of ANK repeats for the tetramerization of TRPV6 and TRPV5 ion channels Erler et al 2004). A very interesting hypothesis for the functional role for the 29 ANK repeat containing Drosophila NOMPC channel is that this repeat structure forms the gating spring of mechanoreceptors (Howard and Bechstedt 2004). Vertebrate TRPA1 channels that are candidates for the mechanosensitive transduction channel of hair cells only contain 17 ANK repeats, which may still confer sufficient gating spring stiffness (Corey et al 2004).…”
Section: Ankyrin Repeatsmentioning
confidence: 99%